Communicating Vegan Utopias: The Counterfactual Construction of Human-animal Futures. Issue 1 (2nd January 2022) - Adams, Matthew
ABSTRACT: Industrialized animal agriculture reveals human-animal relations defined by routinized, institutionalized violence on a staggering scale. Despite greater public recognition of these issues, consumption of meat and other products from industrially processed animals continues to rise globally. This article responds to an ongoing need to consider unexplored sites in research addressing challenges to "meat culture" and the promotion of alternatives. To this end, it examines the film Carnage, about a future vegan utopia, as a distinctive artistic intervention. It is analyzed as a unique example of the construction of counterfactual futures – the practice of imagining the potential impact of hypothetical events on future scenarios. It is claimed that Carnage reflects potential advances in effective animal advocacy, and further innovation in artistic, cultural and methodological interventions that can enliven campaigning repertoires of rhetorical strategies, discursive and narrative frames.